2010
DOI: 10.3892/ol.2010.205
|View full text |Cite
|
Sign up to set email alerts
|

Nordihydroguaiaretic acid inhibits growth of cervical cancer SiHa cells by up-regulating p21

Abstract: Abstract. Nordihydroguaiaretic acid (NDGA) and its derivatives possess anti-cancer effects on various types of cancer via the induction of apoptosis or cell cycle arrest. This study proved that NDGA inhibited cervical cancer SiHa cell growth and induced cell cycle arrest at the G 1 phase, which may be a consequence of cell cycle kinase inhibitor p21 induction. NDGA promoted acetylation of histone H3 in total and p21 gene-associated chromatin. This effect is gene selective, since NDGA has no impact on the p27 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…For instance, NDGA promotes cell death by caspase-3 cleavage in the breast cancer cell lines SK-BR-3 and BT-474 [ 26 ]. In addition, NDGA inhibits growth and induces cell cycle arrest at the G1 phase in cervical cancer-derived cell line SiHa by regulating cell cycle kinase inhibitor p21 and promoting the acetylation of histone H3 [ 27 ]. In the prostate cancer PC3 cell line, NDGA impairs cell migration and tumor metastasis in nude mice via suppressing the function of single-pass transmembrane protein neuropilin 1 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, NDGA promotes cell death by caspase-3 cleavage in the breast cancer cell lines SK-BR-3 and BT-474 [ 26 ]. In addition, NDGA inhibits growth and induces cell cycle arrest at the G1 phase in cervical cancer-derived cell line SiHa by regulating cell cycle kinase inhibitor p21 and promoting the acetylation of histone H3 [ 27 ]. In the prostate cancer PC3 cell line, NDGA impairs cell migration and tumor metastasis in nude mice via suppressing the function of single-pass transmembrane protein neuropilin 1 [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…NDGA is a natural product, which has been reported to inhibit growth of multiple tumors, such as breast cancer, cervical cancer, gastric cancer, lung cancer, prostate cancer, and neuroblastoma. [11][12][13][14][15][16][17][18] In previous studies, we found Nordy, as a synthetic chiral derivative of NDGA, repressed the growth of glioma cells both in vitro and in vivo. 7,[19][20][21] Figure 1), showed stronger inhibitory effects on the growth of GBM cells than Nordy.…”
Section: Ndga-p21 Inhibits Gbm Cell Proliferationmentioning
confidence: 83%
“…Previous studies of NDGA and Nordy suggest that cell cycle arrest, especially G1/S phase arrest, might be one of the underlying mechanisms for NDGA and its analogs to prevent cell proliferation in multiple tumors. 8,11,12,14,22 To determine whether cell cycle arrest was involved in the growth inhibition by NDGA-P21, we applied flow cytometry analysis on the NDGA-P21 treated U87-MG cell to examine their cell cycle status by ModFit software. As compared to DMSO-treated group, cells in G0/G1 phase increased by 19.46% after NDGA-P21 treatment, whereas cells in S phase decreased by 17.82% (Figure 3a).…”
Section: Ndga-p21 Arrests Cell Cycle Of Glioma Cells But With Littlementioning
confidence: 99%
“…fatty acid synthase and LOX enzymes) (Lu et al, 2010). Additionally, NDGA inhibits tumor-relevant receptor tyrosine kinases and downstream signaling related to the IGF-1 receptor and the downstream protein serine/threonine kinase AKT, along with the c-ErbB2/HER2/Neu receptor in breast cancer cells and in tumor-bearing mice (Youngren et al, 2005;Li et al, 2009; NDGA and trastuzumab suppressed proliferation and survival of trastuzumab-refractory cells to a greater degree than either agent alone (Rowe et al, 2008) SiHa cervical cancer cells (grade II squamous cell carcinoma) NDGA 20-100 µM Growth inhibition induced by up-regulating p21 (Gao et al, 2011) Human SW 850 pancreatic and C4-I cervical cancer cells NDGA 25 µM Inhibits anchorage-independent growth of pancreatic and cervical tumor cells. Increases apoptosis (cells exhibiting fragmented DNA at 12 h post-exposure to NDGA).…”
Section: Anti-cancer Effects Of Ndga Are Mediated Also By Tyrosine Kimentioning
confidence: 99%